An Unusual Case of a Large Extraovarian Endometrioma in an Adolescent - Wei-Guo Nicholas Loh; Nira Borok; Lyndal Anderson; Tanushree Rao (Hindawi Limited, 2022)
Endometriosis in adolescents is often underrecognized and is a contributing factor to significant delays in its diagnosis and management. Extraovarian endometrioma is uncommon, especially in the adolescent age range. We report on a rare case of a large extraovarian endometrioma involving the terminal ileum in an adolescent who presented with abdominal pain and a pelvic mass and its subsequent surgical management. It emphasizes the importance of having a broad differential diagnosis and considers endometriosis in any adolescent with pelvic pain and mass, especially in an atypical context. Increased awareness, education, and research on endometriosis in this young population are essential in order to overcome existing challenges in the early diagnosis and optimal management of this chronic gynaecological condition and avoid morbidity associated with advanced disease.